60‐2: A New Concept of In‐Ga‐Zn Oxide Composition for Fabricating High Mobility and Stability FETs. Issue 1 (May 2016) - Ishihara, Noritaka; Tsutsui, Kazuhiro; Takasu, Takako; Tsubuku, Masashi; Yamazaki, Shunpei; Higano, Satoshi; Daisuke, Kurosaki; Shimomura, Akihisa
Abstract : We used new In‐Ga‐Zn oxide composition (In:Ga:Zn = from 4:2:3 to 4:2:4.1) to fabricate bottom‐gate, top‐contact field‐effect transistors with high mobility and stability. Here we discuss these improvements in mobility and stability based on experiments and calculations. We succeeded in fabricating a 513‐ppi in‐cell‐type touch panel using this In‐Ga‐Zn oxide.